Polish research on accounting ethics. Predominating trends and pioneering approaches - Nowak, Marta (Research Papers of Wrocław University of Economics, 2018)
Literature overview presented in this paper aims to identify and explore the main trends and pioneering approaches in Polish scientific literature on accounting ethics. Predominant approach can be characterized as: applied, empiric, praxis-oriented, legallybased and accountant-focused. Research is carried out by scientists specializing in accounting. The main trends are: focusing on two professions (accountant and financial auditor), and two spheres: book-keeping and financial statements, interpreting accounting ethics from practical point of view, as applied ethics, limiting accounting ethics to legal aspects and professional codes
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 177-184
Keywords: accounting ethics; accounting theory; ethics; accounting; moral philosophy; business ethics; professional ethics; etyka rachunkowości; teoria rachunkowości; etyka; rachunkowość; filozofia moralna; etyka biznesu; etyka zawodowa